Notes for a solidarity political economy - Endara, Sebastián (Cooperativismo & Desarrollo, 2016)
Purpose: This article proposes an analytical and critical view of some components of solidarity economy, primarily understood as an activity aimed at the “reproduction of life”. Description: Conceptions that are not coherent with this core of meaning are discussed, while sources that may supplement or strengthen this view are addressed. Point of view: Solidarity economy, understood as the social process that enables reproduction of life, should be assumed multi-dimensionally. In it several elements that allow us to imagine the complex process that involves such vital activity converge, and it is nourished by aspects such as the Andean thought and its rich, deep value network, which lays out principles like relatedness, correspondence, complementarity and reciprocity. Conclusions: Solidarity economy, as opposed to capitalist logic, subsumes economy to life realization. Therefore, it is said that the products of solidarity economy are not only economic, but fundamentally political and cultural.
Keywords: good living; political economy; solidarity economy; Andean thought